2021
DOI: 10.3389/fmicb.2021.672467
|View full text |Cite
|
Sign up to set email alerts
|

“One for All”: Functional Transfer of OMV-Mediated Polymyxin B Resistance From Salmonella enterica sv. Typhi ΔtolR and ΔdegS to Susceptible Bacteria

Abstract: The appearance of multi-resistant strains has contributed to reintroducing polymyxin as the last-line therapy. Although polymyxin resistance is based on bacterial envelope changes, other resistance mechanisms are being reported. Outer membrane vesicles (OMVs) are nanosized proteoliposomes secreted from the outer membrane of Gram-negative bacteria. In some bacteria, OMVs have shown to provide resistance to diverse antimicrobial agents either by sequestering and/or expelling the harmful agent from the bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 69 publications
7
35
0
Order By: Relevance
“…Moreover, bacterial strains that produce outer membrane vesicles have been shown to lead to an altered susceptibility to antimicrobial peptides (e.g. polymyxin B or colistin, shown in several bacteria including E. coli and Salmonella Typhi) ( Manning and Kuehn, 2011 ; Marchant et al, 2021 ). One study found that polymyxin resistance could even be functionally transferred to sensitive bacteria mediated by outer membrane vesicles ( Marchant et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, bacterial strains that produce outer membrane vesicles have been shown to lead to an altered susceptibility to antimicrobial peptides (e.g. polymyxin B or colistin, shown in several bacteria including E. coli and Salmonella Typhi) ( Manning and Kuehn, 2011 ; Marchant et al, 2021 ). One study found that polymyxin resistance could even be functionally transferred to sensitive bacteria mediated by outer membrane vesicles ( Marchant et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…polymyxin B or colistin, shown in several bacteria including E. coli and Salmonella Typhi) ( Manning and Kuehn, 2011 ; Marchant et al, 2021 ). One study found that polymyxin resistance could even be functionally transferred to sensitive bacteria mediated by outer membrane vesicles ( Marchant et al, 2021 ). It is therefore plausible that mechanisms aside from secreted and diffusible enzymes (such as for beta-lactamases) could contribute to re-seeding and plasmid acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bacterial strains that produce outer membrane vesicles have been shown to lead to an altered susceptibility to antimicrobial peptides (e.g. polymyxin B or colistin, shown in several bacteria including E. coli and Salmonella Typhi) (Manning & Kuehn, 2011;Marchant et al, 2021). One study found that polymyxin resistance could even be functionally transferred to sensitive bacteria mediated by outer membrane vesicles (Marchant et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…polymyxin B or colistin, shown in several bacteria including E. coli and Salmonella Typhi) (Manning & Kuehn, 2011;Marchant et al, 2021). One study found that polymyxin resistance could even be functionally transferred to sensitive bacteria mediated by outer membrane vesicles (Marchant et al, 2021). It is therefore plausible that mechanisms aside from secreted and diffusible enzymes (such as for beta-lactamases) could contribute to re-seeding and plasmid acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this previously susceptible strain was subsequently found to express blaOXA-24 and to release blaOXA-24-containing OMVs (35). Similarly, OMV-mediated horizontal gene transfer has also been identified in the oral pathogen Porphyromonas gingivalis (36), E. coli O104:H4 (37), and S. typhi (38).…”
Section: Transport Across the Bacterial Cell Envelopementioning
confidence: 94%